Functional outcomes in children related to self-care, mobility, and social function after stroke in early childhood: a cohort study - Mota, Larissa Audi Teixeira; Silva, Daniela Rodrigues Baleroni; Pfeifer, Luzia Iara (Arquivos de Neuro-Psiquiatria, 2022)
Background: Stroke has been increasingly recognized as an important morbidity and mortality factor in neonates and children. Children have different and more diverse risk factors than adults, commonly related to an underlying disease. Stroke may compromise functional capacity in children. Few studies have focused on functional outcomes related to activities and participation.Objectives: To investigate post-stroke functionality of children related to self-care, mobility, and social function. Methods: We assessed the functional outcome of 14 children younger than 7.5 years who suffered a stroke in early childhood through the use of the Pediatric Evaluation of Disability Inventory (PEDI). Results: The average age of the sample at assessment was 3.6 ± 1.4 years (2 - 6 years). The average scores in the PEDI functional domains of self-care, mobility, and social function were, respectively, 37.6 ± 15.4, 36.2 ± 15.4, and 48.7 ± 11.1. Children showed age-appropriate functional outcomes in the PEDI functional domains: 71.4% of them in self-care and mobility and 92.9% in social function. Children with bilateral injuries (p = 0.05) and longer hospital stays (r = -0.79, p = 0.001) showed the worst scores in PEDI's social function domains. Conclusions: Overall, our sample of preschool children showed age-appropriate functional outcomes on self-care, mobility, and social function domains after stroke. However, children with bilateral injuries and longer hospital stays showed the worst scores in social function domains. We recommend focusing on functional rehabilitation to promote activities and participation and to monitor the development of children's social skills after stroke.
Keywords: Stroke; Child; Self-Care; Locomotion; Social Skills